Patterns of natural regeneration of pine forests in the Left-Bank Forest-Steppe of Ukraine - Volodymyr P. Pasternak; Tetiana S. Pyvovar; Anna V. Garmash (Наукові праці Лісівничої академії наук України)
The study of natural regeneration in pine stands, widespread in the Forest-Steppe of Ukraine, is crucial for transforming forest management towards sustainable, close-to-nature practices. This study aims to reveal the features of the natural regeneration of pine stands in the Left-bank Forest-Steppe of Ukraine, based on data from sample plots in Kharkiv and Sumy regions.